Evaluation of effect of cholecystectomy on common bile duct diameter using ultrasonography and liver function test: a prospective study - Shreyas Bhalerao, Shreyas Bhalerao; Batra, Pooja; Utaal, Maneshwar Singh; Sasan, Chirag (International Surgery Journal, 2018)
Background:Different factors influencing the post cholecystectomy CBD diameter have been implicated. Ultrasound has emerged as a diagnostic imaging method of choice for liver and extrahepatic biliary system. In order to differentiate the diagnosis of asymptomatic bile duct dilatation, one needs to perform either MRCP or ERCP, which are both expensive and/or invasive test. Therefore, it is necessary to understand the physiological changes in bile duct after cholecystectomy to reduce unnecessary testing for early detection of bile duct lesions. Methods: 100 cases of gall stone disease undergoing cholecystectomy in the department of surgery were studied. Pre operative and Post operative Ultrasound whole abdomen with focus on CBD diameter and Liver function test were done, Post operative data was collected on 10th day and again after 3 months. The data was compiled, compared and analysed. Results:The mean preoperative diameter was 4.12 mm, postoperatively, the mean diameter of the CBD in early follow up period i.e. at 10th day and at 3 months, was found to be 4.75 and 5.14 mm respectively. The difference between mean preoperative and mean postoperative (10th day follow up) diameter was found to be 0.63 mm (p<0.01). The difference between mean preoperative and mean postoperative (3 months follow up) diameter was found to be 1.02 (p<0.01) mm, both statistically significant. Conclusions:Significant compensatory dilatation does occur in common bile duct diameter after cholecystectomy in most of the patients.